Adult Neurogenic Lower Urinary Tract Dysfunction and Intermittent Catheterisation in a Community Setting: Risk Factors Model for Urinary Tract Infections - Michael Kennelly; Nikesh Thiruchelvam; Márcio Augusto Averbeck; Charalampos Konstatinidis; Emmanuel Chartier-Kastler; Pernille Trøjgaard; Rikke Vaabengaard; Andrei Krassioukov; Birte Petersen Jakobsen (Advances in Urology)
A risk factor model for urinary tract infections in patients with adult neurogenic lower urinary tract dysfunction performing clean intermittent catheterisation was developed; it consists of four domains, namely, (1) general (systemic) conditions in the patient, (2) individual urinary tract conditions in the patient, (3) routine aspects related to the patient, and (4) factors related to intermittent catheters per se. The conceptual model primarily concerns patients with spinal cord injury, spina bifida, multiple sclerosis, or cauda equina where intermittent catheterisation is a normal part of the bladder management. On basis of several literature searches and author consensus in case of lacking evidence, the model intends to provide an overview of the risk factors involved in urinary tract infections, with specific emphasis to describe those that in daily practice can be handled and modified by the clinician and so come to the benefit of the individual catheter user in terms of fewer urinary tract infections.